Entrepreneurial Literacy, Family Environment, and Entrepreneurial Interest: The Mediating Role of Motivation - Shafa Syahira; Putra Hilmi Prayitno; Lisa Rokhmani; Ro'ufah Inayati (Jurnal Pendidikan Ekonomi, 2024)
Unemployment is a major problem for developing countries, including Indonesia. Various efforts continue to be made, one of which is by fostering an entrepreneurial spirit among adolescents, especially high school students. The study is a quantitative study that aims to examine the effect of entrepreneurial literacy and family environment on entrepreneurial interest and examine the mediating role of entrepreneurial motivation. This study used primary data from a sample of 206 high school students with a purposive sampling technique. The data were collected by distributing questionnaires through Google Forms. Using SEM-PLS analysis techniques, the results show that there is a positive and significant influence between entrepreneurial literacy and family environment on entrepreneurial interest among high school students. In addition, entrepreneurial motivation can mediate the relationship between entrepreneurial literacy and family environment on students' entrepreneurial interest. The implications of this study can be used to develop more effective entrepreneurship programs in high schools, as well as increase the role of families in supporting the development of students' entrepreneurial interests. Keywords: entrepreneurial literacy, family environment, entrepreneurial interest, entrepreneurial motivation